Sociology and military studies classical and current foundations - Soeters, J. (Cass military studies, 2018)
This book examines the connection between sociology and the challenges faced by the modern military. Military studies are taken in a broad sense here, so the volume encompasses a wide range of issues, including civil-military relations, military-political affairs, performance and outcomes of military operations, and organizational arrangements including technology and the composition, performance and well-being of personnel. This book will be of great interest to students of sociology, military studies, civil-military relations, war and conflict studies, and IR in general.